A Cd-reduced hybrid buffer layer of CdS/Zn(O, S) for environmentally friendly CIGS solar cells. Issue 9 (25th September 2017) - Rana, Tanka Raj; Kim, SeongYeon; Kim, JunHo; Kim, Kihwan; Yun, Jae Ho
Abstract : For the fabrication of high efficiency Cu(In, Ga)Se2 (CIGS) solar cells, a Cd-reduced hybrid CdS/Zn(O, S) is used as the buffer layer. Abstract : For the fabrication of high efficiency Cu(In, Ga)Se2 (CIGS) solar cells, a CdS thin film is usually used as the buffer layer. However, since Cd is toxic and also a hazardous material for the environment, Cd-free or Cd-reduced buffer is required for the realization of CIGS solar cells as an environmentally friendly device. We fabricated a Cd-reduced hybrid buffer layer of CdS(Cd-treatment)/Zn(O, S), where CdS was prepared by dipping it into a CdS CBD solution for 2 min and Zn(O, S) was deposited by co-sputtering of ZnO and ZnS. The hybrid buffer provided an improved short circuit current and open circuit voltage and thus high power conversion efficiency. The best CIGS solar cell with the hybrid buffer showed 12.69% cell efficiency compared to the CdS-buffered standard cell with 13.06% cell efficiency. The improved efficiency of the Cd-treated solar cell was found to be a consequence of an enhanced response to blue wavelength photons and surface passivation of the absorber surface by the treatment.